2018
DOI: 10.1186/s12904-018-0355-8
|View full text |Cite
|
Sign up to set email alerts
|

Negative pain management index scores do not necessarily indicate inadequate pain management: a cross-sectional study

Abstract: BackgroundThe Pain Management Index (PMI) is widely used in the assessment of pain management, and negative scores are traditionally considered to indicate inadequate pain management. However, it is not known whether negative PMI scores are always problematic.MethodsIn this prospective observational study, we examined the data of 1156 patients with cancer and pain who were hospitalized in a cancer care hospital in Japan from July 2012 to January 2015 and compared the proportion of patients with PI across vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…However, caution must be exercised when interpreting the results of pain management index. Previous studies have already identified that though pain intensity is expected to decrease as the PMI score increases this is not always true [31]. For example, in this study, only 2.5% of patients were inadequately treated at 24 hours, despite the fact that about 40% needed more analgesics than prescribed at this particular time.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, caution must be exercised when interpreting the results of pain management index. Previous studies have already identified that though pain intensity is expected to decrease as the PMI score increases this is not always true [31]. For example, in this study, only 2.5% of patients were inadequately treated at 24 hours, despite the fact that about 40% needed more analgesics than prescribed at this particular time.…”
Section: Discussionmentioning
confidence: 55%
“…Secondly, Sakakibara, N., et al, have identified that those with –1 score (therefore bad pain control, according to PMI), have scored more pain interference than those with PMI score 0 (good pain control). The authors recommended that when the aim is to identify definitively inadequate care, PMI scores of − 2 and − 3 should be considered, and not scores of − 1 [31]. In addition in spite of receiving strong opioids, previous reports have shown that approximately 85% of patients reported uncontrolled postoperative pain [32, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-related pain (CRP) can be nociceptive pain which comes from the actual damage of nonneural tissues and neuropathic pain which is caused by damage of the somatosensory nervous system [ 3 , 6 , 8 ]. Pain assessment is an integral component of cancer pain management which aims at identifying pain characteristics, pain etiology, specific pain syndromes, and analgesic targets using pain management index (PMI) [ 9 ]. To manage CRP effectively, the WHO has developed a 3-step pain ladder which includes the use of a nonopioid (paracetamol) for mild pain, a weak opioid (Codeine) for moderate pain, and a strong opioid (morphine) for severe pain [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sensitivity of PMI scores of < −1 and < 0 for predicting pain interference were only 0.16 and 0.37, and the corresponding specificities were 0.95 and 0.71, respectively. This implies that a negative PMI does not always indicate inadequate pain management [20].…”
Section: Pain Prevalence: Reasons For Lack Of Improvement In Cancementioning
confidence: 99%